PENGARUH PELATIHAN KERJA DAN PENGEMBANGAN KARIR TERHADAP LOYALITAS KARYAWAN PADA PT. MULTI MAS CHEMINDO MEDAN - Widia Sari; Ananda Fitriani Dewi (Jurnal Widya, 2024)
This research aims to determine the effect of job training and career development on employee loyalty at PT. Multi Mas Chemindo Medan. The number of samples used in this research was 150 research samples. The data collection techniques used in this research used questionnaires and observation. The testing technique used in this research uses research instrument tests, descriptive statistical tests, classical assumption tests, multiple linear regression UI and hypothesis testing. The data sources in this research use secondary and primary data sources. The results of this hypothesis research show that job training and career development variables have a positive and significant effect on employee loyalty. The results of the simultaneous tests can be concluded that together they have a positive and significant effect on employee loyalty.